2021
DOI: 10.3389/fcimb.2021.571901
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Invasive Non-typeable Group B Streptococcus Isolates From Denmark (2015 to 2017)

Abstract: The number of invasive Streptococcus agalactiae (GBS) non-typeable (NT) isolates in Denmark received since 1999 has in general accounted for 10% of all invasive GBS isolates. We present data on 55 clinical NT isolates based on clinical manifestations, clonal relationship, antimicrobial resistance (AMR) determinants, and virulence factors. The GBS isolates included in this study were phenotypic-based NT obtained from 2015 to 2017, as well as 10 reference isolates. Whole genome sequencing (WGS) was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(91 reference statements)
1
6
0
Order By: Relevance
“… 35 , 36 Recent advances in molecular techniques have enhanced the capabilities of epidemiological analysis of the origin of GBS isolates. 11 , 37 In this case, our results showed that the GBS isolates from the infant bloodstream and maternal breast milk had a high consistency in homology analysis. However, the GBS isolates from the mother’s perinatal cervical secretion exhibited differences in homology analysis.…”
Section: Discussionsupporting
confidence: 51%
“… 35 , 36 Recent advances in molecular techniques have enhanced the capabilities of epidemiological analysis of the origin of GBS isolates. 11 , 37 In this case, our results showed that the GBS isolates from the infant bloodstream and maternal breast milk had a high consistency in homology analysis. However, the GBS isolates from the mother’s perinatal cervical secretion exhibited differences in homology analysis.…”
Section: Discussionsupporting
confidence: 51%
“…Twelve studies were conducted across the WHO European region, mainly in the Netherlands [13, 14], Denmark [15, 16] and Sweden [17, 18]. Likewise, six studies originated from the WHO Western Pacific [19–24] and Americas regions [7–11, 25, 26] ().…”
Section: Resultsmentioning
confidence: 99%
“…No study originated from the African, Eastern Mediterranean or Southeast Asian regions. Twelve studies [7, 14–16, 19, 21, 22, 25, 27–30] only investigated the genomic epidemiology of GBS in diseased adults, whereas the remaining considered GBS concomitantly in non-pregnant populations and neonates and/or pregnant women (8–11, 13, 17, 18, 20, 23, 26, 31–33; ). Overall, a total of 14 208 participants were described across the included studies, with a total of 14 110 GBS isolates being analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-genome sequencing was performed as previously described ( Fuursted et al, 2016 ; Slotved et al, 2021 ). Briefly, genomic DNA was extracted using a DNeasy Blood & Tissue Kit (QIAGEN, Hilden, Germany), and fragment libraries were constructed using a Nextera XT Kit (Illumina, San Diego, CA, USA) followed by either 150 or 250 bp paired-end sequencing on either the MiSeq or NextSeq 550 platform (Illumina, San Diego, CA, USA), respectively, according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%